Application of Low-Dose CT and MRI in the Evaluation of Soft Tissue Injury in Tibial Plateau Fractures. (16th September 2022) - Qi, Yinping; He, Peipei; Zhu, Jianping; Wang, Yanan; Zhao, Hong; Chen, Junbo
Abstract : Objective . To explore the application value of low-dose CT and MRI in the evaluation of soft tissue injury in tibial plateau fractures. Methods . This study included 89 patients with high suspicion of TPF and KI admitted to our hospital from July 2015 to May 2021. After arthroscopy, 81 patients were diagnosed with FTP combined with KI. The Schatzker classification based on X-ray and CT plain scan combined with three-dimensional reconstruction was recorded, and the soft tissue injury was recorded according to the MRI examination of the affected knee joint. Results . With the results of pathological examination and arthroscopic surgery as the gold standard, the results of MRI and pathological examination and arthroscopic examination were in good agreement (Kappa = 0.857, 0.844 ), and CT was moderately in agreement (Kappa = 0.697, 0.694 ). In KI examination, CT and MRI had no difference in the evaluation of ligament injury and bone injury (P > 0.05 ), but MRI had better diagnostic effect on meniscus injury (P < 0.05 ). Finally, the satisfaction survey showed that patients in the CT group were more satisfied with clinical services (P < 0.05 ). Conclusion . Both CT and MRI have certain diagnostic value for occult tibial plateau fractures, among which CT examination is more advantageous for trabecular bone fractures, MRI examination is more advantageous for cortical bone fractures, and MRI examination can improve occult tibial plateau fracture inspection accuracy.